Protection of Medical Facilities and Personnel in Gaza Conflict: Humanitarian Law Perspective - Gunawan, Yordan; Aditama, Setiyantoro Wahyu; Mareto, Irvan (Media Iuris, 2025)
The ongoing conflict in Gaza has significantly exacerbated the humanitarian crisis, particularly impacting the health sector. This study examines the forced expulsion of medical personnel from hospitals by the Israeli army in Gaza on December 25, 2024, which raises serious concerns regarding violations of international humanitarian law. This article analyzes the role of the International Committee of the Red Cross (ICRC) in safeguarding medical personnel and health facilities during armed conflicts, with a particular focus on the application of the Geneva Conventions. Employing a normative legal approach and case study method, this research utilizes international legal instruments, ICRC reports, and independent assessments of the Gaza conflict. The findings revealed that the expulsion of medical personnel violates fundamental principles of international humanitarian law, specifically concerning the protection of medical services in conflict zones. This study highlights the critical role of the ICRC in addressing such violations and ensuring that medical personnel can carry out their duties safely. Furthermore, it emphasizes the necessity of strengthening enforcement mechanisms and imposing sanctions against perpetrators to uphold the integrity of international humanitarian law.